Efektivitas Konsentrasi dan Frekuensi Pemberian Larutan Pupuk Kandang pada Hidroponik Tanaman Kailan (Brassica oleraceae var. alboglabra) Sistem Deep Flow Technique (DFT): Effectiveness of Manure-Based Nutrient Solution Concentration and Application Frequency in Deep Flow Technique (DFT) Hydroponic Cultivation of Kailan (Brassica oleracea var. alboglabra) - wuryantoro wuryantoro; Elysa Aulia Pramesti; Indah Rekyani Puspitawati (JURNAL AGRI-TEK : Jurnal Penelitian Ilmu-Ilmu Eksakta, 2025)
Kailan (Brassica oleracea var. alboglabra) is a high-value vegetable that has the potential to be developed through the Deep Flow Technique (DFT) hydroponic system by utilizing goat manure solution as an environmentally friendly nutrient alternative. The study aims to determine the effect of the interaction of concentration and frequency of application of goat manure solution on the growth and yield of kailan plants, and to determine the extent to which it can compete with AB-Mix. The study was conducted at the  Greenhouse of Agricultral Faculty, University of Merdeka Madiun.  in October–December 2024. The experiment  using a two-factor of Randomized Block Design (RBD) with three replications. The first factor was the concentration of goat manure solution (1 kg/20 L, 3 kg/20 L, and 6 kg/20 L air) and the second factor was the frequency of application every 3 days, 6 days, and 9 days, plus one AB-Mix control treatment. The results showed that the frequency of application every 6 days (F6) provided a more significant increase in yield with an increase in the concentration of goat manure up to 6 kg/(P6) compared to frequencies of 1 and 3 kg. The best results were achieved by a combination of 6 kg concentration treatment with a frequency of application every 6 days, and was able to compete with the application of AB-Mix. Thus, the use of manure solution can substitute the use of chemical nutrients, is cheaper, easier to obtain and more sustainable.